2020
DOI: 10.1021/jacs.0c02351
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Artificial Carboligases Facilitate Regioselective Preparation of Enantioenriched Aldol Adducts

Abstract: Controlling regio- and stereoselectivity of aldol additions is generally challenging. Here we show that an artificial aldolase with high specificity for acetone as the aldol donor can be reengineered via single active site mutations to accept linear and cyclic aliphatic ketones with notable efficiency, regioselectivity, and stereocontrol. Biochemical and crystallographic data show how the mutated residues modulate the binding and activation of specific aldol donors, as well as their subsequent reaction with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Examples are a new family of abiological carbene and nitrene transferases (mentioned above) or artificial carboligases. The latter enzyme family, that arose from a de novo computationally designed retro-aldolase followed by extensive laboratory evolution, catalyzes multistep reactions utilizing covalently linked enamines and Schiff base intermediates that are formed from chiral intermediate species. , , The formation of these chiral intermediate species was not considered at all during the initial rational design procedure, and thus, the enzyme active site was not optimized to properly stabilize them. This could also be one of the reasons why de novo enzymes often perform less efficiently as compared to Nature and laboratory evolved variants. ,, …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Examples are a new family of abiological carbene and nitrene transferases (mentioned above) or artificial carboligases. The latter enzyme family, that arose from a de novo computationally designed retro-aldolase followed by extensive laboratory evolution, catalyzes multistep reactions utilizing covalently linked enamines and Schiff base intermediates that are formed from chiral intermediate species. , , The formation of these chiral intermediate species was not considered at all during the initial rational design procedure, and thus, the enzyme active site was not optimized to properly stabilize them. This could also be one of the reasons why de novo enzymes often perform less efficiently as compared to Nature and laboratory evolved variants. ,, …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[14,18] In addition, for protein catalysts, it has been reported that a single mutation can alter the substrate scope and the reaction stereoselectivity. [19] Varied directionalities may originate from differences in a type of substrate specificity. For example, the degree of differences in K m values and/or binding affinities between the starting materials and product (i. e., the aldehyde used for the aldol reaction and the aldol product) may result in differences in the apparent rates at certain concentrations.…”
Section: Working Hypothesismentioning
confidence: 99%
“… [3] Since then, numerous in vitro and in vivo studies based on focused libraries in microtiter plates (MTPs) have been reported. [4] Selected examples include 1) the directed evolution of sortase A to improve its robustness and activity by focused loop engineering and head‐to‐tail backbone cyclization, [5] 2) the directed evolution of enantiospecific enzymes,[ 6 , 7 , 8 ] 3) the directed evolution of P450 for various applications,[ 9 , 10 , 11 , 12 ] and, more recently, 4) the directed evolution of a de novo designed retro‐aldolase, [13] of a metalloenzyme for enantiospecific ester hydrolysis designed from short peptides, [14] and of a metalloenzyme for olefin metathesis using an expanded nitrobindin variant. [15] Lately, directed evolution finds also increased use in the biotechnological field: for example, the process and enzyme engineering approach applied to galactose oxidase for the biocatalytic transformation of 5‐hydroxymethylfurfural (HMF), a valuable building block in the synthesis of materials from renewable resources.…”
Section: Introductionmentioning
confidence: 99%